Federalismo fiscal e o discrepo na descentralização da educação pública no Brasil no século XXI: evolução dos gastos e das matrículas no ensino básico e superior - Lima Filho, Gilvan Dias de (2013)
The redemocratization, the economic opening and stability and the reconfigurations of state functions with duties reduction and competence rise were peremptory issues to new Brazilian federative relation implemented from the 1988-Federal-Constitution on, which was marked by the implementation of an extensive redistribution of tax funds, but, with a wide binding on the allocation of them, in addendum of states and especially the municipalities. Within this context, the present study aims to evaluate the correlation between the levels of expenses on public education in Brazil from 2000 to 2011, with quantitative equivalence of students enrolled in each governmental domain (federal, state and municipal) and in each type of education (basic education and higher education). The implemented methodology has materialized as an explicative one, for the purpose of the research, as bibliographical and documentary concerning the procedures for data collection, and concurrently qualitative and quantitative regarding how to address and answer the problem. The applied statistics were based on the use of descriptive actions, with the use of graphs, tables and measures of position. As results, it was found multiple antagonisms between the correlation of the amount of resources and the total enrollment effectuated. As an empirical fact, in 2011 the municipal sphere accounted for 52.48% of all students enrolled and 35.60% of the active volume of expenditure on education. In parallel, the federal sphere had as attribute 2.67% of students placed in public schools and universities and 24.38% of the granted income. As a result, the investment per capita per student promoted for that year, for federal level, was 13.55 times higher than for municipal level. Performing similar analogy for teaching modalities, there are similarly latent abrupt deformities. While a student enrolled in elementary school in 2011 from the federal system received annual investment equivalent to R$ 24,079.94, at the state instance amounted to R$ 3,384.85 and at the municipal instance R$ 3,189.14, representing improper distinction potentials for formation. Adding to this, as a backdrop mismatches in intergovernmental transfers made by conditional and inflexible manner and the absence of any parameter of quality in the training of students and professionals involved with education. Thus, it gets to the current conjuncture of Brazilian education, with the country showing up far to assert the principle of equal opportunities intrinsic with primary function of education and fiscal Federalism.